1985
DOI: 10.1021/np50042a001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Scission by Bleomycin Group Antibiotics

Abstract: Certain properties of the bleomycin analogs deglycobleomycin A2 and decarbamoylbleomycin A2 have been characterized. In common with bleomycin A2, both deglycobleomycin A2 and decarbamoylbleomycin A2 were found to mediate DNA degradation in the presence of Fe(II) + O2. Both analogs were found to have essentially the same sequence selectivity for DNA strand scission as bleomycin A2 when a 5'-[23P]-end-labeled linear duplex DNA derived from SV40 DNA was employed as a substrate. Product analysis for the three anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 19 publications
2
44
1
Order By: Relevance
“…Thus, no functional role for the gulopyranose can be assigned based on structural analysis. Nonetheless, an important role for the disaccharide moiety in DNA-binding and cleavage by HOOFe(III)⅐bleomycin has been indicated by the reduced DNA cleavage activity of deglycobleomycin in vitro (35,36). One possibility is that the gulopyranose serves as a ''space-filling'' unit allowing the metal binding domain to adopt an optimized and stabilized orientation relative to the target C4Ј-H. We further note that the respective orientations and intramolecular hydrogen-bonding interactions of the metal-binding and disaccharide domains of Co⅐BLM bound to 1 are similar to those observed in the crystal structure of Cu(II)⅐bleomycin bound to a bleomycin resistance protein (37) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no functional role for the gulopyranose can be assigned based on structural analysis. Nonetheless, an important role for the disaccharide moiety in DNA-binding and cleavage by HOOFe(III)⅐bleomycin has been indicated by the reduced DNA cleavage activity of deglycobleomycin in vitro (35,36). One possibility is that the gulopyranose serves as a ''space-filling'' unit allowing the metal binding domain to adopt an optimized and stabilized orientation relative to the target C4Ј-H. We further note that the respective orientations and intramolecular hydrogen-bonding interactions of the metal-binding and disaccharide domains of Co⅐BLM bound to 1 are similar to those observed in the crystal structure of Cu(II)⅐bleomycin bound to a bleomycin resistance protein (37) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 and Table 1), and their comparison with the BLM A2 spectroscopic data reported in the literature (30) confirmed that the isolated intermediate indeed represents 3-MOP-decarbamoyl-BLM. Decarbamoyl-BLM has previously been reported as a partial hydrol- ysis product of BLM under basic aqueous conditions after prolonged storage but has only been accessible in very small quantities (35,36). Additionally, decarbamoyl-BLM demethyl-A2, lacking one methyl group in the A2 terminal amine, was isolated as a byproduct during the tedious multi-step total chemical synthesis of BLM demethyl-A2 (37).…”
Section: ϫ8mentioning
confidence: 99%
“…Although several in vitro studies have shown that deglyco-BLMs exhibit reduced DNA cleavage activities compared with BLM A2 or B2 (36,39,40), the role of the carbamoyl group remained controversial. Decarbamoyl-BLM was reported to show significantly reduced malondialdehyde forming activity, but similar oligonucleotide cleavage activity compared with BLM A2 (36), and similar DNA cleavage activity as BLM in the presence of Fe 2ϩ , but reduced activity in the presence of Cu 2ϩ and dithiothreitol (39), and oligonucleotide cleavage activities much closer to deglyco-BLM A2 rather than BLM A2 (41). Our results obtained with 3-MOP-decarbamoyl-BLM, however, indicate a significant impact of the carbamoyl group on DNA cleavage activity resulting in ϳ10-fold reduced plasmid relaxation efficiency compared with BLM A2 and B2.…”
Section: ϫ8mentioning
confidence: 99%
“…Further mechanistic assays were performed for the pure compounds 1 to 4 in the DNA methyl green (10), the DNA strandscission (12) and in the topoisomerase I inhibition assays (10). Then, in order to determine if cytotoxicity to KB cells was due to the capacity of the compounds to interact with DNA, a colorimetric microassay was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…DNA strand-scission assay: The DNA strand-scission assay was adapted from a previously described procedure (12). Briefly, samples were dissolved in DMSO and assayed at 100, 10 and 1 mg/ml.…”
Section: Biological Evaluationmentioning
confidence: 99%